Applications and Innovations in Intelligent Systems XIV Proceedings of AI-2006, the Twenty-Sixth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence - Tuson, Andrew (New York : Springer, 2006)
Annotation The papers in this volume are the refereed application papers presented at AI-2006, the Twenty-sixth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2006. The papers in this volume present new and innovative developments in the field, divided into sections on Data Mining and Bayesian Networks; Genetic Algorithms and Optimisation Techniques; Agents and Semantic Web; and Natural Language. This is the fourteenth volume in the Applications and Innovations series. The series serves as a key reference as to how AI technology has enabled organisations to solve complex problems and gain significant business benefit. The Technical Stream papers are published as a companion volume under the title Research and Development in Intelligent Systems XXIII.
Trade